Development of an arteriolar niche and self-renewal of breast cancer stem cells by lysophosphatidic acid/protein kinase D signaling - Yinan Jiang (Nature Portfolio, 2021)
Jiang, Guo, Hao et al. investigate the role of the tumour microenvironment in breast cancer stem cell regulation and identify an arteriolar niche in which BCSCs tended to be enriched in human estrogen receptor positive breast cancer. Here, BCSCs are found to interact with arteriolar endothelial cells through LPA/PKD-1 signalling-mediated arteriolar differentiation of ECs and self-renewal of BCSCs.